Design and Manufacture of Electric Car Chasis Frame for Two Passengers With Solidworks Modeling 2020 - Zaenuri, Ahmad; Sunardi, Ade; Kasum (Journal of Global Engineering Research and Science, 2022)
An electric car is a car that is driven by a DC motor using energy stored in thebattery. The use of electric cars is considered more effective in addition to notcausing air pollution and a simpler engine construction and as an alternativemeans of transportation. The frame/chassis is the main part of the car thatfunctions to support other components such as the engine, battery, steeringsystem, braking system, driver's seat and other vehicle equipment, and also asa vibration damper if the vehicle runs on various types of road surfaces andvarious modes of motion. From the vehicle, the frame used is a ladder framewhich has a simpler and stronger structure. This study aims to design andmanufacture the frame of an electric car and analyze the load received and themaximum load that the frame can withstand. This research begins with thedesign of the frame, then the assembly of the frame will be carried out thendata will be collected on the frame which will then be processed to determinethe load received by the frame and analyze the value of the welding stress onthe frame.